Metode Community-Based Research dalam Pemberdayaan Perempuan Pengrajin Ecoprint di Era Digital (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2025)
This study discusses the application of the Community-Based Research (CBR) method in empowering women ecoprint artisans in the digital era. Ecoprint as a batik technique based on natural materials has great economic and environmental potential, but its development is often hampered by limited access to technology, marketing, and capital. Through the CBR approach, the community is placed as an equal partner in every stage of research, from problem identification, technical training, to digital mentoring. The results of the study show that there is an increase in the production capacity of craftsmen, both in the variety of techniques, quality consistency, and production management efficiency. In addition, the digital marketing skills gained allow ecoprint products to reach a wider market through social media and online platforms, thereby increasing competitiveness and building awareness of the importance of branding. The social impacts that arise include increased confidence, group solidarity, and the role of women in economic decision-making, while the economic impact can be seen in increasing household income and opening up new distribution opportunities. Thus, the application of CBR is not only academically relevant, but also practical in strengthening the independence of women ecoprint artisans in the digital era.
Keywords: Women's empowerment; Ecoprint artisans; Community-Based Research; Digital mentoring; Local product marketing